Quarterly Earnings Information, Stock Returns and Stock Market Efficiency: An Empirical Study - Iqbal; Mallikarjunappa, T. (Gyan Management Journal, 2008)
This paper examines quarterly earnings information,lock -returns, and stock marke efficiency in India by taking quar erly earnings announcement as an event. The study is based on 1.52 companies having minimum 20 percent foreign holdings. The companies are divided into good n ws, bad news and overall portfolios. We have used event study m thodology, t test, Runs test, sign test, raw r turns and log r turns. The behaviour of AARs and CAAR are examin d for 30 days before and 31 days af er the announcement of quarterly earnings. The results of th study contradict semi-strong form of efficient market hypothesis.